2008
DOI: 10.1016/j.jvs.2007.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Infrainguinal vein graft stenosis: Cutting balloon angioplasty as the first-line treatment of choice

Abstract: Cutting balloon angioplasty is a reasonable, initial treatment for infrainguinal vein graft stenosis in most patients. It is a safe, minimally invasive, outpatient procedure with patency rates that are comparable to OS and superior to PTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…16,32 Studies of CBA, however, systematically excluded longer lesions. 20,30,33 Our results extend the findings of CBA for treatment of stenoses in infrapopliteal grafts and, by using receiver operating characteristic analysis, we were able to more rigorously determine the lesion length associated with restenosis. Given the lower rates of mortality and MACE in patients with shorter compared to those with longer lesions, lesion length in this cohort may reflect a greater systemic burden of disease.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…16,32 Studies of CBA, however, systematically excluded longer lesions. 20,30,33 Our results extend the findings of CBA for treatment of stenoses in infrapopliteal grafts and, by using receiver operating characteristic analysis, we were able to more rigorously determine the lesion length associated with restenosis. Given the lower rates of mortality and MACE in patients with shorter compared to those with longer lesions, lesion length in this cohort may reflect a greater systemic burden of disease.…”
Section: Discussionsupporting
confidence: 71%
“…First reported by Engelke et al in 2002, CBA of infrainguinal graft stenosis has subsequently been shown to have acceptable short-time patency rates, superior to standard balloon angioplasty and comparable to open surgical revision in selected patients. 29,30 Positive results have not been uniformly observed, however, and even though the use of cutting balloons may provide good early results, CBA use does not eliminate the late risk of restenosis. 20,31 …”
Section: Discussionmentioning
confidence: 99%
“…Schneider et al [14] reported that 50% of failing grafts were detected within 1 year after bypass. Based on this observation, they recommended more frequent DUS examinations of the vein graft within the first 1 or 2 years after LE bypass grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Mills et al [13] reported that the proximal and the distal anastomosis was similar in frequency of stenotic lesions. According to Berkowitz et al [15] and Schneider et al [14], 40% of stenotic lesions were located within 4 cm of the proximal anastomosis due to the location of venous valves or intraoperative vein graft injury from clamping or manipulation. However, Avino et al [2] and Berceli et al [10] reported that stenotic lesions were most commonly seen midgraft due to the diameter of the vein graft and the location of the vein valve.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the last few years, a new system of balloon angioplasty has emerged; based on a controlled and less traumatic dilation of the lesion, cutting balloon angioplasty (CBA) has the potential to improve the outcome of catheter-based therapy by minimizing elastic recoil and achieving better angiographic results. [7][8][9] To the best of our knowledge, there are no reports about the efficacy of CBA in infrapopliteal lesions involving the arterial bifurcations. Hence, the aim of our pilot study was to evaluate the safety, feasibility, and effectiveness of the cutting balloon in the management of infrapopliteal bifurcation lesions.…”
Section: Introductionmentioning
confidence: 99%